Validated stability indicating gradient RP-HPLC method for the estimation of antihypertensive drugs in bulk and pharmaceutical dosage forms - Raj, Napa Delhi; Anbazhagan, Sockalingam; Babu, Kunapareddy Anudeep; Babu, Sunkara Narendra; Bhimanadhuni, Chusena Narasimharaju (International Current Pharmaceutical Journal, 2012)
A rapid and precise RP-HPLC method for determination of Olmesartan medoxomil and Hydrochlorothiazide in bulk and pharmaceutical dosage forms. Olmesartan medoxomil & Hydrochlorothiazide are found to be degraded together under different set of conditions as followed according to ICH guidelines and the degradants so formed along with olmesartan & hydrochlorothiazide are separated by using INERTSIL ODS C18 3V (150 x 4.6, 5µ) using mobile phase 1ml triethanolamine in one litre water and the pH was adjusted to 2.5 with orthophosphoric acid and acetonitrile using a gradient program with a flow rate of 1ml/min, throughout the gradient program with a detection wavelength of 225nm for both the compounds with a injection volume of 10µl. The method was validated for selectivity, linearity, accuracy, robustness, precision and specificity. The results were indicating the method was selective in analysis of both olmesartan medoxomil and hydrochlorothiazide in the presence of degradation products formed under various stress conditions. DOI: http://dx.doi.org/10.3329/icpj.v1i11.12058 International Current Pharmaceutical Journal 2012, 1(11): 336-341